Advances in rapid sex-steroid action : new challenges and new chances in breast and prostate cancers - Migliaccio, Antimo; Castoria, Gabriella (Springer New York, 2012)
Rapid actions of sex steroids play a critical role in mediating the biological outcome of target tissues. This book reviews the importance of these non-genomic effects in initiation and progression of breast and prostate cancers. Particular emphasis is placed on discussing how rapid steroid actions not only impact disease development and response to conventional therapies for these two types of cancers, but have also led to the identification of potential new therapeutic targets and treatment possibilities for cancer patients. The book reviews the fundamental basis of target development and the current status of these studies, which are providing valuable insights in key areas of breast and prostate cancers. Particular emphasis is placed on discussing how rapid steroid actions not only impact disease development and response to conventional therapies for these two types of cancers, but have also led to the identification of potential new therapeutic targets and treatment possibilities for cancer patients. The book reviews the fundamental basis of target development and the current status of these studies, which are providing valuable insights in key areas of breast and prostate cancers.